ACTUALIZATION OF KH. ABDURRAHMAN WAHID'S (GUS DUR) THOUGHT: SOCIO-RELIGIOUS AND ECONOMIC EDUCATION PERSPECTIVE - Muhammad Fahmi Hidayatullah (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
Character and economic crises are felt in almost every country. Learn from KH. Abdurrahman Wahid, a religious leader (ulama ') and state leader (umara'), is able to provide an example in caring for unity and integrity through the social, religious and economic fields. Gus Dur's thoughts were born from a boarding school that was able to join Western and Middle Eastern thought through the education he had received. Returning to Indonesia to become a Muslim intellectual, cultural observer, and politician who ordered him to become the fourth president of the Republic of Indonesia. This research method uses descriptive qualitative with the type of character study or literature review with Gus Dur's thoughts in the social, religious and economic fields as the object of his research. Gus Dur's idea in the social and religious aspects is pluralism in uniting the nation. Meanwhile, in the economic aspect, the increase in the country's economic growth starts at -3% to grow by 4.9%. In addition, Gus Dur was very persistent in eradicating corruption by ordering the TGPTPK team even though he was disbanded due to threats. And regarding the prevention of collusion and nepotism, Gus Dur is willing to lose his position rather than violating the constitution.Keywords: Actualization; Gus Dur; Socio-Religion and Economy. AbstrakKrisis karakter dan ekonomi hampir dirasakan setiap negara. Belajar dari KH. Abdurrahman Wahid seorang pemuka agama (ulama’) dan pemimpin negara (umara’) mampu memberikan contoh dalam merawat persatuan dan kesatuan melalui bidang sosial, agama, dan ekonomi. Pemikiran Gus Dur lahir dari pondok pesantren yang mampu dikombinasikan dengan pemikiran Barat maupun Timur Tengah melalui Pendidikan yang telah dikenyamnya. Kembali ke Indonesia menjadi seorang intelektual muslim, budayawan, dan politisi yang mengatarkannya menjadi presiden keempat Republik Indonesia. Metode penelitian ini menggunakan kualitatif deskriptif dengan jenis penelitian studi tokoh atau kajian literatur dengan menjadikan pemikiran Gus Dur bidang sosial, agama, dan ekonomi sebagai objek penelitiannya. Gagasan Gus Dur dalam aspek sosial dan agama adalah pluralism dalam mempersatukan banga. Sementara dalam aspek ekonomi peningkatan pertumbuhan ekonomi negara diawali -3% sampai tumbuh 4,9%. Selain itu, Gus Dur sangat gigih dalam melakukan pemberantasan korupsi melalui pembentukan tim TGPTPK walaupun dibubarkan karena dianggap sebagai ancaman. Dan perihal pencegahan kolusi dan nepotisme, Gus Dur merelakan kehilangan jabatannya dibandingkan melanggar konstitusi.Kata Kunci: Aktualisasi; Gus Dur; Sosio-Religi dan Ekonomi.